Determination Strategy for Controlling Bloodstock Components Packed Red Cell Using Monte Carlo Simulation - Hanif Awandani; Helia, Vembri Noor; Ibrahim, Faisal (Jurnal Sistem Teknik Industri, 2022)
Blood supply is an important part that is very influential on health because almost all blood types are necessary for medical activities. This condition makes blood management very important, but improper blood management can cause a waste that results in huge final costs and causes losses for both the customer and the blood supplier. In this case, Monte Carlo simulation can be used to develop several policies that can optimize blood inventory levels and minimize inventory costs at Indonesian Red Cross XYZ. In this simulation, input data required are blood donor supply and Packed Red cells (PRC) demand data, this data will be used to determine the shortage and expired rate. From simulation will be obtained shortage rate of 33 blood bags and an expired rate of 75 blood bags with inventory cost Rp. 36,226,964. Monte Carlo simulation will make new policy rules with increasing the supply of whole blood (WB) which will be used as a component of the PRC and reducing the supply level. From these simulation results, the best policy will gain and applied at PMI XYZ to optimize inventory cost.